ASR gene family: a case of tandem-drive evolution - Barros, Nicolle Louise Ferreira; Filgueiras, João Pedro Carmo; Trenz, Thomaz Stumpf; Weber, Guilherme; Turchetto-Zolet, Andreia Carina; Margis-Pinheiro, Marcia (Frontiers in Molecular Biosciences, 2025)
IntroductionABA, Stress, and Ripening (ASR) proteins are characterized by the presence of the ABA/WDS domain and are involved in plant development processes and tolerance to abiotic and biotic stresses. Despite their importance as transcription factors or molecular chaperones, a complete understanding of their biological roles is limited by a lack of information on their mechanisms of action, protein structure, and evolutionary relationships between family members. Our previous molecular dynamics simulation analysis of rice OsASR5 suggested that H91, R92, H93, and K94, are the main residues involved in the interaction with DNA, essential for the transcription factor activity of this protein. However, the presence and conservation of the DNA-binding domain among ASR family members remain unknown. Likewise, there is a lack of phylogenetic analyses evaluating the evolutionary history of ASR proteins across major taxonomic groups, outside just the Solanum species.MethodsTo address these gaps, we conducted a phylogenetic study and protein sequence analyses to gain insights into the evolution of ASR genes in plants. We performed a genome-wide identification of ASR genes via HMMER, using the ABA/WDS domain, in 163 Archaeplastida genomes.Results and discussionOur results reveal that the potential origin of the ASR gene occurred in the common ancestor of Streptophytes (Charophytes and Embryophytes). Moreover, our study identifies ASR genes in seedless plants. The evolutionary relationship between 465 ASR homologs, found in 76 species, was estimated through maximum likelihood analysis. The results reinforce the rapid and dynamic evolution of the ASR gene family, reflected by the low support in the deep nodes of the phylogeny and the great variation in the number of ASRs in the genomes evaluated, and in some cases their complete absence. As for diversification, tandem duplications seem to be the main mechanism involved. Regarding the conservation of residues in the domain, only two of the 78 are widely conserved, such as E79 and H93. By analyzing the three-dimensional model, we noticed the interaction between them and we hypothesize that they are essential for the stabilization of the domain during interaction with DNA.